How to ensure basic competencies in end of life care: a mixed methods study with post-graduate trainees in primary care in Germany - Schwill, Simon; Reith, Dorothee; Walter, Tobias; Engeser, Peter; Wensing, Michel; Flum, Elisabeth; Szecsenyi, Joachim; Krug, Katja (BMC palliative care, 2020)
Background: Providing end of life care (EoLC) is an important aspect of primary care, which reduces the risk of hospital admission for most patients. However, general practitioners (GPs) seem to have low confidence in their ability to provide EoLC. Little is known about an adequate volume and kind of training in EoLC among GP trainees. - Methods: We performed a before-after comparison in all post-graduate GP trainees who were registered in the vocational training program (KWBW VerbundweiterbildungPLUS). They were offered participation within a two-day seminar focussing on palliative care in 2017. Those who attended the seminar (intervention group I) completed a paper-based questionnaire directly before the intervention (T1) and 6 months after (T2). None-attendees (group C) were also asked to fill out the questionnaire once. The questionnaire covered previous experiences in palliative care, self-assessment of competencies in EoLC in the organisation of patient care as well as in control of symptoms, attitudes towards death and caring for dying patients and questions about GPs’ role in EoLC. - Results: In total, 294 GP trainees (I: n = 219; C: n = 75) participated in the study. Of those, more than 90% had previously gained experience in EoLC mainly during vocational training in the hospital rotation. Around a third had previously gained competencies in EoLC in medical school. Between groups I (T1) and C no significant differences were observed in socio-demographic characteristics, pre-existing experience or overall expertise. At T2, 75% of participants of group I declared they have extended their competencies in EoLC after the intervention and 70% classified the intervention as helpful or very helpful. Overall, they rated their competencies significantly higher than at T1 (p < 0.01). In detail, competencies in organisation of EoLC and competencies in handling of symptoms significantly improved (p < 0.01). Due to the intervention, 66% could reflect their attitudes towards dying, death and grief and 18% changed their attitudes. Group I highlighted palliative care as one of GPs tasks (Likert 4.47/5, SD 0.75). - Conclusions: The intervention fostered personal competencies, understanding and self-confidence in EoLC among GP trainees. This is crucial for the aim to broadly provide EoLC.